2020
DOI: 10.1186/s13020-020-00319-9
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Chinese medicine Biqi capsule compared with leflunomide in combination with methotrexate in patients with rheumatoid arthritis: a randomized controlled trial

Abstract: Background: Biqi capsule is a traditional Chinese medicine widely used as a complementary and alternative treatment for rheumatoid arthritis (RA). The objective is to understand the efficacy, safety and mechanism of Biqi combined with methotrexate (MTX) in RA. Methods: We present a randomized, controlled pilot trial on Biqi combined with MTX against patients with active RA. Seventy patients were randomized 1:1 to receive Biqi + MTX or Leflunomide (LEF) + MTX for 24 weeks, and were assessed at baseline, 4, 12 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…[ 6 ] Animal studies have found that BQC exerts a protective effect on articular cartilage by downregulating cartilage oligomeric matrix protein levels in serum, cartilage oligomeric matrix protein expression in synovium and cartilage, and inhibiting inflammatory infiltration, synovial proliferation, and joint destruction. [ 24 ] MTX is a commonly used DMARDs class of drugs in clinical practice, and clinical studies have demonstrated synergistic effects of MTX in combination with paralysis capsules, [ 11 , 13 ] but rigorous randomized, double-blind controlled studies to evaluate their long-term efficacy are lacking. Therefore, a prospective, randomized, double-blind, single-simulation randomized controlled study would be conducted to investigate the long-term efficacy and safety of BQC in combination with MTX compared to MTX alone in the treatment of RA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 6 ] Animal studies have found that BQC exerts a protective effect on articular cartilage by downregulating cartilage oligomeric matrix protein levels in serum, cartilage oligomeric matrix protein expression in synovium and cartilage, and inhibiting inflammatory infiltration, synovial proliferation, and joint destruction. [ 24 ] MTX is a commonly used DMARDs class of drugs in clinical practice, and clinical studies have demonstrated synergistic effects of MTX in combination with paralysis capsules, [ 11 , 13 ] but rigorous randomized, double-blind controlled studies to evaluate their long-term efficacy are lacking. Therefore, a prospective, randomized, double-blind, single-simulation randomized controlled study would be conducted to investigate the long-term efficacy and safety of BQC in combination with MTX compared to MTX alone in the treatment of RA.…”
Section: Discussionmentioning
confidence: 99%
“…[ 10 ] BQC is a commonly used Chinese materia medica preparation for the treatment of RA in China and has been approved by the State Food and Drug Administration as a complementary therapy for RA due to its good efficacy and low side effects. [ 11 ] BQC consists of Radix Notoginseng (San Qi), Strychni Semen (Ma Qian Zi), Codonopsis pilosula (Franch.) Nannf (Dang Shen), Rhizoma Atractylodis Macrocephalae (Bai Zhu), Radix Salviae Miltiorrhizae (Dan Shen), Rhizoma Chuanxiong (Chuan Xiong), and Radix Glycyrrhiza (Gan Cao), which have significant anti-inflammatory, antiswelling and analgesic effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has the functions of nourishing qi and blood, dispelling wind and dehumidifying, promoting blood circulation, and relieving pain. Modern pharmacological research has found that, [ 14 ] Biqi capsule can promote the production of tissue inhibitor of metalloproteinase-1, reduce the expression of interleukin 1 and matrix metalloproteinase-3, so as to protect articular cartilage and improve inflammation, [ 15 ] it can also effectively regulate the ability of physical coordination and immune function, [ 16 ] and has less adverse reactions. [ 17 – 19 ] Therefore, we intend to evaluate the efficacy and safety of Biqi capsule in the treatment of KOA by this randomized controlled trial.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, metabonomics has been widely used in the research of disease phenotype, biomarker discovery of drug toxicology, metabolism phenotype and physiological function of experimental animals, comprehensively depicting the overall characteristics of metabolism [23,24]. In order to study the metabolic mechanism of dyslipidemia and try to nd the key biomarkers in the intervention of Gegen Qinlian decoction on dyslipidemia.…”
Section: Introductionmentioning
confidence: 99%